Analisis Six Sigma untuk Mengurangi Cacat Produk dan Peningkatan Kualitas di Pabrik Gula XYZ - Mardiansyah, Bagas Tri; Muttaqin, Aan Zainal; Susanto, Doni (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the application of the Six Sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) approach in reducing product defects and improving production quality at PG. XYZ. The main problem in sugar production is the high level of defects in the form of non-uniform sugar grains and non-uniform sugar color, which has an impact on decreasing efficiency and customer satisfaction. Defect data was analyzed using a control chart (P-Chart), DPMO value calculation, and sigma level to evaluate process stability. The results showed that the production process was not statistically stable, with an average defect rate of 3.65% and a sigma value at level 2.5. The main causes of defects were identified through Fishbone Diagram analysis and obtained from human, machine, method, material, and environmental factors. The proposed solutions include the creation of SOPs, operator training, machine calibration, and routine monitoring and audit systems. This study is expected to be a reference for other sugarcane processing industries in implementing the Six Sigma method to improve product quality and competitiveness.